Compliance of Lebanese Pickling Industry with Lebanese and International Standards - Sami Tlais; Hayat Omairi; Ali Al Khatib; Hassan HajjHussein (Turkish Journal of Agriculture: Food Science and Technology)
In light of recent news reporting the use of banned colorants in Lebanese-made pickled turnips exported to the European Union (EU) by the Rapid Alert System of Food and Feed (RASFF), The Lebanese Consumer Protection Association tested samples of pickled turnips being sold to the public and confirmed the use of rhodamine B. Many products were pulled off the market and were replaced with new products that were supposed to be free of any banned colorants. We selected 5 different brands of pickled turnips and tested them for pH, salinity, nitrites, and colorants. We tested the salinity using two methods: evaporation and titration. The concentration of nitrites was tested by absorbency method. The presence of colorants was determined using TLC and absorbency method. We determined that the newly released pickled turnips comply with the rules and regulations adopted by the Lebanese Standards Institution (LIBNOR) and the international standards according to the Codex Alimentarius.